Effect of Storage Containers on Quality of Household Drinking Water in Urban Communities in Ibadan, Nigeria - Olanrewaju Onigbogi; Oluwatoyin Ogunyemi (International Journal of Public Health Science (IJPHS), 2014)
The method of storage is essential in maintaining water purity and safety for drinking purposes. This study assessed the effect of various storage containers on household drinking water quality in a resource-limited setting. A quasi-experimental design was adopted. Four communities using protected springs as household drinking water sources were purposively selected. Forty-four households were selected and randomly assigned to four treatment groups; namely Covered Buckets with Taps (CBT), Covered Buckets without Tap (CB), Covered Kegs with Taps (CKT) and Covered Kegs without Tap (CK).  Physicochemical analysis and bacteriological analysis were carried out on the water samples before and after they were put in the containers. Data was analyzed using SPSS version 12. At baseline, mean pH values of water samples from the springs and RSC were 6.4±0.6 and 7.1±0.7 respectively which were above the recommended. Mean chloride concentration of springs (14.3±7.4mg/l) and RSC (19.3±10.0 mg/l) samples were below recommended. Mean Total Coliform Count (TCC) of the springs in the four communities was 18.0±4.0 and mean TCC of RSC was 12.7±4.9. Five percent of water samples from RSC had mean E.coli count of 100/100ml. The mean TCC after introducing CB, CBT, CK and CKT in all the communities were 10.0±4.0, 8.5±4.2, 6.9±2.8 and 7.3±3.7 respectively (p<0.05). The use of covered kegs without tap was best in reducing contaminants in drinking water. Education on appropriate household drinking water storage and handling practices is recommended.